2013
DOI: 10.1590/s0034-8910.2013047004136
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentos em Língua Brasileira de Sinais para avaliação da qualidade de vida da população surda

Abstract: OBJECTIVE:To construct versions of the WHOQOL-BREF and WHOQOL-DIS instruments in Brazilian sign language to evaluate the Brazilian deaf population's quality of life. METHODS:The methodology proposed by the World Health Organization (WHOQOL-BREF and WHOQOL-DIS) was used to construct instruments adapted to the deaf community using Brazilian Sign Language (Libras). The research for constructing the instrument took placein 13 phases: 1) creating the QUALITY OF LIFE sign; 2) developing the answer scales in Libras; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
4
0
4
Order By: Relevance
“…In a study for adaptation of an instrument on quality of life into LIBRAS, the researchers found it difficult to make such adjustment. The authors reported limitations, because Brazilian Portuguese and LIBRAS are different languages, with different language expressions and structures (19) . Also, the authors of the battery of instruments that was used to evaluate the reading comprehension of the deaf individuals stressed that there is a lack of instruments for assessment of sign languages (10,17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study for adaptation of an instrument on quality of life into LIBRAS, the researchers found it difficult to make such adjustment. The authors reported limitations, because Brazilian Portuguese and LIBRAS are different languages, with different language expressions and structures (19) . Also, the authors of the battery of instruments that was used to evaluate the reading comprehension of the deaf individuals stressed that there is a lack of instruments for assessment of sign languages (10,17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Para isso, traduziram o WHOQOL para língua de sinais, visando melhor caracterizar a qualidade de vida dos surdos, levando em consideração as particularidades da cultura da população surda. Um instrumento traduzido para a língua de sinais proporciona autonomia linguística aos sujeitos, possibilitando que os próprios surdos dimensionem e classifiquem seu bem-estar 16,17 . 20 .…”
Section: Discussionunclassified
“…Another study, conducted by Brazilian researchers, constructed and validated LIBRAS versions of the WHOQOL-BREF and WHOQOL-DIS instruments, to evaluate the quality of life of the Brazilian population with deafness. These validations have the potential to optimize the accessibility of people with deafness, including participation in research projects and their access to information ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%